PENGARUH KUALITAS PRODUK MANDIRI MOBILE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MENJADI NASABAH BANK MANDIRI (Studi Kasus pada Nasabah Bank Mandiri KCP Semarang Majapahit) - Tavisar, Latanba Via; Prihatini, Apriatni Endang; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Mandiri Mobile provides convenience but often is constrained by barriers of the use of technology, as well as service performance often does not suitable with customer’s expectations so that the number of complaints from customers and Bank Mandiri KCP Semarang Majapahit’s third-party funds target is not reached. Therefore it is necessary to know how big the influence of product quality of Mandiri Mobile and service quality to decision to become customer. Type of this research is explanatory research. Data collection technique using questionnaires which was distributed to 100 respondent with purposive sampling method by the way of accidental sampling. Data analysis consisted of validity, reliability crosstabs, simple linear regression, multiple linear regression, coefficient determination, t test and F test using SPSS for Windows version 16.0. The conclusions of this research is product quality of Mandiri Mobile and service quality has a positive and significant influences to decision to become customers, both of partially and simultaneously, where product quality of Mandiri Mobile gives bigger influence to the decision to become customer rather than service quality. Suggestions can be submitted are should increase the completeness of transaction’s types in Mandiri Mobile and reducing to ask and speak with other staff while serving customers.